Influence of the Belt and Road Initiative on the energy trade between China and Latin America - Haoyu, Zheng; Gerdel, Aymara (Sinología hispánica. China Studies Review, 2022)
Energy is the basis and driving force for the progress of humanity, it is vital for economic development, for people’s lives, and for the national security of countries. This research will analyze a set of variables that affect the behavior of Latin American energy exports to the People’s Republic of China during the period 2000 -2019 using a log-linear model. The results show that assuming a real growth of China’s gross domestic product (GDP) close to 7% per year, Latin American energy exports to China would grow by 4% per year on average. Assuming an average annual increase of 5% in China’s energy production, Latin American energy exports to China are estimated to increase by 5.9%. With respect to energy consumption in China, assuming a 7% increase, it is estimated that energy exports from Latin America to China would grow by 8.2%. This model also estimates the elasticity of energy exports according to the behavior of energy prices, China’s investment in Latin America and the projects developed by the Asian country in the region.